2020
DOI: 10.1653/024.103.0401
|View full text |Cite
|
Sign up to set email alerts
|

A Volatile Semiochemical Released by the Fungus Garden of Leaf-Cutting Ants

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Often, after identifying these allelochemicals, they are used as tools in pest management (36). In the leaf-cutter ant literature as well, the approach has been largely from the direction of behavior to mechanism, and it has been suggested that the cultivar uses volatile semiochemicals to communicate with the ant colony (37) but attempts at identifying these have not been conclusive (38,39). Our approach was different.…”
Section: Lipid Changes Between Fungal Garden and Gongylidiamentioning
confidence: 99%
“…Often, after identifying these allelochemicals, they are used as tools in pest management (36). In the leaf-cutter ant literature as well, the approach has been largely from the direction of behavior to mechanism, and it has been suggested that the cultivar uses volatile semiochemicals to communicate with the ant colony (37) but attempts at identifying these have not been conclusive (38,39). Our approach was different.…”
Section: Lipid Changes Between Fungal Garden and Gongylidiamentioning
confidence: 99%
“…Often, after identifying these allelochemicals, they are used as tools in pest management ( 36 ). In the leaf-cutter ant literature as well, the approach has been largely from the direction of behavior to mechanism, and it has been suggested that the cultivar uses volatile semiochemicals to communicate with the ant colony ( 37 ), but attempts at identifying these have not been conclusive ( 38 , 39 ). Our approach was different.…”
Section: Discussionmentioning
confidence: 99%
“…We further tested the hypothesis that the cultivar reinforces optimized nutritional provisioning by signalling its nutritional needs to its ant farmers. Here, we tested two key predictions: (1) the cultivar signals by synthesizing fatty acid compounds with low volatility that provide information at local scales of small garden patches where mulch is deposited (Khadempour et al, 2021;North et al, 1999;Richard et al, 2004;Sousa et al, 2020), and (2) the cultivar concentrates fatty acids in swollen hyphal cells called gongylidia (bundled into staphylae) that are key nutritional rewards consumed by ants (Mueller et al, 2001;Schiøtt & Boomsma, 2021). We then evaluated the fungal cultivar's role in provisioning its ant farmers by tracking the fate of nutrients beyond the initial substrate deposition stage as they travel through leafcutter farming systems.…”
Section: Introductionmentioning
confidence: 99%